Nanggeleh: Kajian Filosofis dan Psikologi Dakwah Petani Pandalungan - Abdul Ghofur; Zainil Ghulam; Bambang Subahri (Institut Agama Islam Syarifuddin Lumajang, 2022)
Nanggeleh is a local term for the Pandalungan community which means plowing agricultural land. A term that is full of philosophical symbolic meanings and involves long term memory from a psychological perspective so as to form behavior that is in accordance with the principles of Da'wah Islamiyah. This research is a qualitative type of research with interview, observation and documentation data collection methods conducted in Ranuyoso Village, Ranuyoso District, Lumajang Regency. This study discusses 1). Nanggeleh's Philosophical Concepts and Practices in the Muslim Community of Pandalungan and 2). Psychology of Da'wah and Contextualization of Nanggeleh Farmers Pandalungan.